KARAKTERISASI ENZIM GLUKOAMILASE YANG DIPRODUKSI OLEH Amylomyces rouxii DARI RAGI DALAM MENGHIDROLISIS PATI MENTAH - , NORMAN HOLSTEINA, Dr. Ir. Retno Indrati, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Most of sugar industries still used gelatinized starch as a substrate for its processed, especially in saccarification process. To provide the gelatinized starch, its need heating process that requires high energy and cost. Therefore, its need a study about hydrolysis raw starch by amylase enzyme. Amylomyces rouxii was known having an ability to grow on raw substrate medium and produced glucoamylase enzyme. The aims of this research are to determine hydrolysis capability of glucoamylase enzyme from Amylomyces rouxii in various raw starch substrates effects of temperature and pH variation on enzyme activity during starch hydrolysis process, and also stability of the enzyme to temperature and storage time. Firstly, 0,5ml substrate (tapioca, sago, maizena, and soluble starch concentration 2%) and 0,5ml glucoamylase enzyme are reacted at 370C, pH 6,5 for 30 min. Secondly, hydrolysis process was variated at various temperature (room temperature, 300C, 370C, 450C) and pH (pH 4